2006
DOI: 10.1002/pmic.200500558
|View full text |Cite
|
Sign up to set email alerts
|

Human colostrum: Identification of minor proteins in the aqueous phase by proteomics

Abstract: Human colostrum is an important source of protective, nutritional and developmental factors for the newborn. We have investigated the low abundance proteins in the aqueous phase of human colostrum, after depletion of the major proteins secretory IgA, lactoferrin, alpha-lactalbumin and HSA by immunoabsorption, using 2-D LC and gel-based proteomic methods. One hundred and fifty-one proteins were identified, 83 of which have not been previously reported in human colostrum, or milk. This is the first comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
99
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 53 publications
3
99
0
Order By: Relevance
“…Yamada used immunosorbent assay method to remove high-abundance proteins (β-CN and immune globulin), and identified low-abundance proteins in colostrum and normal milk, and the results showed that colostrum contained specific proteins, such as β-chains of fibrinogen, α-antitrypsin, gelsolin and Apo lipoprotein by 2-DE separation and mass spectrometry and micro-sequence (Yamada et al, 2002). In the study of human colostrum, 151 of whey protein were identified, in which 83 species is not discovered before by immune adsorption removal of high abundance ratios proteins (such as immune globulin, lactalbumin, lactoferrin and human serum albumin protein) (Palmer et al, 2006). Therefore, the detection of low abundance proteins has important significance for comprehensive understanding milk proteins.…”
Section: Analysis Of Milk Low-abundance Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yamada used immunosorbent assay method to remove high-abundance proteins (β-CN and immune globulin), and identified low-abundance proteins in colostrum and normal milk, and the results showed that colostrum contained specific proteins, such as β-chains of fibrinogen, α-antitrypsin, gelsolin and Apo lipoprotein by 2-DE separation and mass spectrometry and micro-sequence (Yamada et al, 2002). In the study of human colostrum, 151 of whey protein were identified, in which 83 species is not discovered before by immune adsorption removal of high abundance ratios proteins (such as immune globulin, lactalbumin, lactoferrin and human serum albumin protein) (Palmer et al, 2006). Therefore, the detection of low abundance proteins has important significance for comprehensive understanding milk proteins.…”
Section: Analysis Of Milk Low-abundance Proteinsmentioning
confidence: 99%
“…Boesman-Finkelstein obtained lactoferrin from skim off casein human whey by SDS-PAGE(Boesman-Finkelstein and Finkelstein, 1982). David began to study skim milk trace protein, detected the effect with removing high abundance ratio proteins by SDS-PAGE method, lactoferrin was observed on electrophoresis map before the removal of colostrum (Palmer et al, 2006). …”
Section: Lactoferrin Proteomicsmentioning
confidence: 99%
“…Chitinase-3 like 1, known as cartilage glycoprotein-39 in humans, is detected in chondrocytes and synovial cells, as well as lung, heart, infant brain and placenta. Approaches such as immunoabsorption (Murakami et al, 1998;Palmer et al, 2006;Yamada et al, 2002), solution isoelectric focusing (IEF) (Zuo and Speicher, 2002), affinity tagging (Holland et al, 2006;Conte-Junior et al, 2006), and semi-coupled anion-and cation-exchange chromatography (Fong et al, 2008) have been used to remove the dominant proteins and increase the relative abundance of the minor proteins, to aid proteomic analysis of complex samples such as bovine milk. Proteomic methodology has been used in the study and characterization of proteins from milk and dairy products (Yamada et al, 2002;Manso et al, 2005;Fong et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…lactoferrin, α-lactalbumin and serum albumin from human colostrum, allowing the identification of 151 proteins, over half of which have not been previously identified in colostrum or in milk (Palmer et al, 2006). Following fractionation, substantial attention has been given to the identification of minor (including bioactive) components in milk.…”
mentioning
confidence: 99%